2010
DOI: 10.1371/journal.pone.0011736
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling HIV Vaccines in Brazil: Assessing the Impact of a Future HIV Vaccine on Reducing New Infections, Mortality and Number of People Receiving ARV

Abstract: BackgroundThe AIDS epidemic in Brazil remains concentrated in populations with high vulnerability to HIV infection, and the development of an HIV vaccine could make an important contribution to prevention. This study modeled the HIV epidemic and estimated the potential impact of an HIV vaccine on the number of new infections, deaths due to AIDS and the number of people receiving ARV treatment, under various scenarios.Methods and FindingsThe historical HIV prevalence was modeled using Spectrum and projections w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Of note, this study queried participants about their attitudes on and willingness to encourage a 90 % effective vaccine; some previous research indicates that a vaccine of lower efficacy (actual or perceived) may prompt less risk compensation [3538]. The degree of risk compensation necessary for off-setting the positive effect of a partial, highly efficacious vaccine is likely great [3, 39, 40], particularly when vaccine coverage is high [1, 41]. Thus, although the prospect of developing a vaccine with full efficacy currently appears bleak, continued effort in vaccine development is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, this study queried participants about their attitudes on and willingness to encourage a 90 % effective vaccine; some previous research indicates that a vaccine of lower efficacy (actual or perceived) may prompt less risk compensation [3538]. The degree of risk compensation necessary for off-setting the positive effect of a partial, highly efficacious vaccine is likely great [3, 39, 40], particularly when vaccine coverage is high [1, 41]. Thus, although the prospect of developing a vaccine with full efficacy currently appears bleak, continued effort in vaccine development is certainly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A preventive HIV vaccine could make a substantial impact on the epidemic [13]. However, given that the first vaccines are likely to be only partially effective, successful dissemination among men who have sex with men, people who inject drugs (PWID), and high-risk heterosexual populations will be critical [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, early vaccines on the market are likely to be only partially effective, and post-vaccination increases in risk behavior (i.e., risk compensation (Hogben & Liddon, 2008)) could reduce the public health benefit (Andersson et al, 2007; Blower, Schwartz, & Mills, 2003; Eaton & Kalichman, 2007; Fonseca et al, 2010; Gray et al, 2003). Findings from previous studies examining individuals’ likelihood of risk compensation have been mixed; when queried about others’ behaviors, study participants reported a likely increase in sexual risk behavior if vaccinated (Koniak-Griffin, Nyamathi, Tallen, González-Figueroa, & Dominick, 2007; Newman et al, 2009; Newman, Roungprakhon, Tepjan, Yim, & Walisser, 2012; Olin et al, 2006; Sayles, MacPhail, Newman, & Cunningham, 2010; Webb, Zimet, Mays, & Fortenberry, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The International AIDS Vaccine Initiative (IAVI) and the Futures Institute have worked together to develop a mathematical model to study the potential impacts of an HIV vaccine on the pandemic both globally [4], and in countries such as Kenya, China, Uganda and Brazil [5]. In Kenya, IAVI developed this research in collaboration with the Kenya HIV and AIDS Research Coordinating Mechanism (KARSCOM) and a team of researchers at the Kenya AIDS Vaccine Initiative (KAVI) led the technical work with assistance from the Futures Institute.…”
Section: Introductionmentioning
confidence: 99%